How Do Social Support and Transfer Motivation Drive Training Effectiveness among Workers with Disabilities in Indonesia? - Kania Salsabila; Ahmad Shalahuddin; Arman Jaya; Nurul Komari; Mazayatul Mufrihah (CV. Ulil Albab Corp, 2026)
Training programs for workers with disabilities are widely promoted to enhance labor market inclusion; however, empirical evidence explaining the mechanisms underlying training effectiveness remains limited, particularly in developing contexts such as Indonesia. This study examines how social support and training transfer motivation influence training effectiveness by integrating the Unified Model of Task-Specific Motivation and the Capability Approach. A quantitative cross-sectional survey was conducted among 106 Indonesian workers with disabilities who had participated in at least one formal training program. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess direct, indirect, and moderating effects. The results indicate that social support does not directly influence training effectiveness but significantly enhances training transfer motivation, which in turn positively affects training effectiveness and fully mediates the relationship. Transfer design does not significantly moderate the proposed relationships. These findings suggest that training effectiveness among workers with disabilities is primarily driven by motivational mechanisms that transform contextual support into sustained work application. The study contributes to disability-inclusive HRM literature by highlighting transfer motivation as a central explanatory mechanism for effective training outcomes.